Pengaruh Karakteristik Individu, Kecerdasan Emosional Dan Lingkungan Kerja Terhadap Kinerja Pegawai Pada Kantor Dinas Pekerjaan Umum Dan Penataan Ruang (PUPR) Kabupaten Bima - Lia Lestari; Mulyadin Mulyadin (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2023)
This study aims to determine and analyze the influence of individual characteristics, emotional intelligence and work environment on employee performance at the Office of Public Works and Spatial Planning (PUPR) Bima Regency. The population of this study were all employees of the Public Works and Spatial Planning (PUPR) Office of Bima Regency, totaling 204 employees. The sample in this study were 89 employees who were determined based on a purposive sampling technique. Data collection was carried out through observation, interviews, questionnaires, and literature study. Data analysis techniques used in this study were validity test, reliability test, classic assumption test, multiple linear regression analysis, correlation coefficient, determination coefficient, t test, and f test which were processed using SPSS version 20.0. From the results of the study, the following results were obtained: (1) Individual characteristics partially influence employee performance at the Public Works and Spatial Planning Office (PUPR) of Bima Regency. (2) Emotional intelligence has no partial effect on employee performance at the Public Works and Spatial Planning (PUPR) Office of Bima Regency. (3) the work environment has a partial effect on employee performance at the Public Works and Spatial Planning (PUPR) Office of Bima Regency.